Spontaneous Hematomas in COVID-19 Patients on Low-Molecular-Weight Heparin - Hitesh Taleja; Vipin Venugopal Nair; Sunanda Yadav; Raghavendra Venkatnarayanan; Nilanjan Roy; Pankaj Rao (Dubai Medical Journal)
Background: COVID-19 patients are at increased risk of coagulopathy. This coagulopathy may be due to a severe pro-inflammatory state (cytokine storm) and/or by viral sepsis. This can sometimes lead to consumption coagulopathy and decreased platelet count, leading to increased risk of bleeding and may manifest like hematomas in atypical locations. These bleeding manifestations may be spontaneous or can be induced by even minor trauma. Cases: It is a single-center retrospective analysis. Four patients with a confirmed diagnosis of COVID-19 depicting increased risk of bleeding manifestations were included. Patients in our study were managed as per guidelines recommended by the Ministry of Health and Family Welfare Directorate General of Health Services, Government of India. Results: All patients were male. The mean age was 56 ± 18.64 years. One patient was managed conservatively with discontinuation of anticoagulants, volume resuscitation, and transfusion of blood products. Drainage with incision was done for 2 patients. One was managed with pigtail drainage. Conclusion: The effect of anticoagulants given in therapy and their varied presentations are discussed in this article. The article concludes that we need vigilant observation to identify this complication in the early period, resulting in successful management.